Um modelo para avaliação da usabilidade a partir de dados reais de interação dos usuários - Kronbauer, Artur Henrique; Santos, Celso A. S. (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2011)
This paper presents an ongoing PhD work involves interface evaluation based on real user interaction data, including contextual aspects. The model involves aspects of usability metrics establishment, mapping and instrumentation of the application’s source code from experts' interaction, final user interaction capture and analysis of the results obtained. The objective is to automatically gather quantitative data so that can be analyzed in a qualitative and subjective way, making it possible to detect usability problems and measure the quality of use of the interfaces.